PENINGKATAN KEMAMPUAN MENULIS CERPEN MELALUI TEKNIK PENGANDAIAN DIRI SEBAGAI TOKOH DALAM CERITA DENGAN MEDIA AUDIO VISUAL PADA SISWA KELAS X4SMKN 1 SAMPANG - Yuniarto Wiryo Nugroho; Masluhin; Resi Apriani Hergita Candra Candra (Metalanguage: Jurnal Ilmu Bahasa dan Sastra Indonesia, 2022)
In general, in formal situations high school students still have difficulty writing their ideas and ideas properly. This is also experienced by most students of SMKN 1 Sampang The difficulty in writing short stories is caused by 3 factors, namely: teacher factors, student factors, media factors and the techniques used in the teaching and learning process. The problems experienced by students include difficulty issuing ideas, running out of material, not knowing how to start writing a story, and difficulty composing sentences in good and correct Indonesian. The problem experienced by the teacher is that they do not respond to short story writing lessons so they are often skipped, do not use available media, are less creative in developing students' self-potential. Based on the description above, the problems expressed in this study are 1) whether the use of audio-visual media with self-concept techniques as a character in the story can improve the ability to write short stories, and 2) is there an effect of using audio-visual media with self-concept techniques as a character in writing short stories to changes in student behavior in the learning process of writing short stories. The objectives of this study were 1) to describe the improvement of the ability to write short stories through the technique of self-conceptualization as a character in the story using audio-visual media, and 2) to describe the effect of using self-concept techniques as characters in stories with audio-visual media in writing short stories.